How does collaborative governance scale? - Ansell, Christopher K. 1957-; Torfing, Jacob 1963- (New perspectives in policy and politics, 2018)
Explores the role of scale and scaling in collaborative governance, focusing on a wide range of policy areas with cases drawn from Asia, Australia, Europe, and North and South America